The Fossil Fishes of the “Rocha” Collection Housed in the Museu Nacional and the Types Described by Jordan & Branner in 1908 - Polck, Márcia Reis (Universidade Federal do Rio de Janeiro, 2022)
In 1908, D.S. Jordan & J.C. Branner described the following species of fossil fishes from the Araripe Basin: Calamopleurus vestitus, Cearana rochae, Enneles audax, and Tharrias araripis. Such material of the “Rocha Collection”, that was made by Francisco Dias da Rocha (1869-1960), were passed on to the Government of the State of Ceará. In 1961, Carlos de Paula Couto, negotiated the donation of the paleontological collections for the Museu Nacional. We review herein the history of the fossil fishes of the “Rocha Collection” that was housed in the Museu Nacional in, with an emphasis on type material. The documents and literature were consulted, and the fossil fishes were examined and photographed. This material corresponds to 12 catalogue numbers, three of which are replicas of the type- material housed in the Department of Geology, California Academy of Sciences, in California. The remaining nine numbers encompass 27 specimens referring to original material. The represented taxa are: Vinctifer comptoni, Notelops brama, Cladocyclus gardneri, Rhacolepis buccalis, Tharrhias araripis, and Brannerion sp. The only type material found was Cearana rochae, currently a synonym of Tharrhias araripis. This historical rescue of the “Rocha” collection type material will facilitate the investigation of researchers studying the paleoichthyofauna of the Araripe Basin.